An Analysis on the Implementation of Ease of Doing Business in the Province of La Union, Philippines - Flores, Christian Kent (Technium Social Sciences Journal, 2025)
The Ease of Doing Business and Efficient Government Service Delivery Act of 2018 aims to streamline government services' current systems and procedures. This descriptive-quantitative of research assessed the implementing Local Government Units in the Province of La Union with RA 11032 regarding the Citizen's Charter, access to government services through frontline services, Report Card Survey, and Zero Contact Policy. Documentary analysis and survey questionnaire were used to gather the needed data from the 216 frontline personnel. The data were statistically analyzed and interpreted using frequency count, rank, percentages, and median. The following results were determined: (1) LGUs in the Province of La Union are fully implemented and adhered to EODB in terms of the Citizen's Charter, access to government services through frontline services, Report Card Survey; and Zero Contact Policy; (2) the top three causes on the implementation encountered were lacking documentary requirements, clients prefer old system and internet not yet centralized/fully established/upgraded/low connectivity. The findings led to crafting an innovative program to effectively implement the EODB act in local government units in the Province of La Union.